Using Telemetry Sensors Mapping the Energetic Costs in European Sea Bass (Dicentrarchus labrax), as a Tool for Welfare Remote Monitoring in Aquaculture - Alfonso, Sébastien; Zupa, Walter; Spedicato, Maria Teresa; Lembo, Giuseppe; Carbonara, Pierluigi (Frontiers in Animal Science, 2022)
Physiological real-time monitoring could help to prevent health and welfare issues in farmed fishes. Among physiological features that can be of interest for such purpose, there is the metabolic rate. Its measurement remains, however, difficult to be implemented in the field. Thus, mapping the fish acceleration recorded by tag with the oxygen consumption rate (MO2) could be promising to counter those limitations, and to be used as a proxy of energy expenditure in aquaculture environment. In this study, we investigated the swimming performance (Ucrit), the swimming efficiency (Uopt, COTmin) and we estimated the metabolic traits (standard and maximum metabolic rates, SMR and MMR, as well the absolute aerobic scope, AS) of European sea bass (Dicentrarchus labrax; n=90) in swimming tunnel. Among all tested fish, 40 fish were implanted with acoustic transmitter to correlate the acceleration recorded by the sensor with the MO2. In this study, the mean SMR, MMR and AS values displayed by sea bass were 89.8, 579.2 and 489.4 mgO2 kg-1 h-1 respectively. The Uopt and COTmin estimated for sea bass were on average 1.94 km h-1 and 113.91 mgO2 kg-1 h-1. Overall, implantation of sensor did not alter fish swimming performance or induced particular stress, able to increase MO2 or decrease swimming efficiency in tagged fish. Finally, acceleration recorded by tag has been successfully correlated with MO2 and fish mass using sigmoid function (R²=0.88). Overall, such results would help for real-time monitoring of European sea bass health/welfare in aquaculture environment in a framework of precision livestock farming.